2017
DOI: 10.1123/wspaj.2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of High Intensity Functional Training and Circuit Training on Health and Performance Variables in Women: A Pilot Study

Abstract: High intensity functional training (HIFT) emphasizes constantly varied, high intensity, functional activity by programming strength and conditioning exercises, gymnastics, Olympic weightlifting, and specialty movements. Conversely, traditional circuit training (TCT) programs aim to improve muscular fitness by utilizing the progressive overload principle, similar movements weekly, and specified work-to-rest ratios. The purpose of this investigation was to determine if differences exist in health and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
4
20
1
Order By: Relevance
“…33 Murawska-Cialowicz et al 33 also showed an increase in VO 2max for women, which was not observed in men, and no improvements were seen in the blood profile of 11 college students (six men) after 14 weeks of ECPs training. 34 Similar results were achieved by Sobrero et al 35 on body composition (no changes in fat mass and little increase in body mass) after 6 weeks of ECPs training. Sobrero et al 35 also found no changes in maximal oxygen uptake (VO 2max ), anaerobic power and flexibility.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…33 Murawska-Cialowicz et al 33 also showed an increase in VO 2max for women, which was not observed in men, and no improvements were seen in the blood profile of 11 college students (six men) after 14 weeks of ECPs training. 34 Similar results were achieved by Sobrero et al 35 on body composition (no changes in fat mass and little increase in body mass) after 6 weeks of ECPs training. Sobrero et al 35 also found no changes in maximal oxygen uptake (VO 2max ), anaerobic power and flexibility.…”
Section: Introductionsupporting
confidence: 67%
“…34 Similar results were achieved by Sobrero et al 35 on body composition (no changes in fat mass and little increase in body mass) after 6 weeks of ECPs training. Sobrero et al 35 also found no changes in maximal oxygen uptake (VO 2max ), anaerobic power and flexibility. The impact of at least 6 months of ECPs training on pelvic floor muscle strength and support in nulliparous healthy women was evaluated by Middlekauff et al .…”
Section: Introductionsupporting
confidence: 67%
“…Goins [17] similarly reported an 11% increase in VO 2max in recreationally active individuals after 6 weeks of HIFT. Sobrero et al [18] reported no change in VO 2max in recreationally active women after a HIFT program of similar length. Crawford et al [19] also reported no statistically significant improvements in VO 2max after a 9-week HIFT program in untrained adults; however, VO 2max was not assessed with a metabolic cart.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a 2.4% decrease in body fat percentage was observed, primarily due to a 2.2% increase in lean body mass. Sobrero et al [18] observed a 12.54% decrease in body fat percentage following 6 weeks of HIFT, which was also due to an increase in lean body mass. These findings are similar to those of traditional resistance training programs, where improvements in body fat percentage are largely attributed to increases in lean body mass with little change in fat mass [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Functional-Fitness has been increasingly growing in popularity as it is considered a more enjoyable form of exercise when compared with traditional aerobic and resistance training [17]. In addition, it is done in a shorter period of time inducing similar positive outcomes reported in strength [18], performance [19] and body composition [20] compared to longer duration more traditional type resistance and aerobic type workouts. To the best of our knowledge, this is the first study designed to examine RPE as a viable tool for controlling the intensity of a metabolic training session in trained men.…”
Section: Correlations Between Rpe and Physiological Variablesmentioning
confidence: 99%